Arginine methylation catalyzed by PRMT1 is required for B cell activation and differentiation. Issue 1 (December 2017) - Infantino, Simona; Light, Amanda; O'Donnell, Kristy; Bryant, Vanessa; Avery, Danielle; Elliott, Michael; Tangye, Stuart; Belz, Gabrielle; Mackay, Fabienne; Richard, Stephane; Tarlinton, David
Abstract Arginine methylation catalyzed by protein arginine methyltransferases (PRMT) is a common post-translational modification in mammalian cells, regulating many important functions including cell signalling, proliferation and differentiation. Here we show the role of PRMT1 in B-cell activation and differentiation. PRMT1 expression and activity in human and mouse peripheral B cells increases in response to in vitro or in vivo activation. Deletion of thePrmt1 gene in mature B cells establishes that although the frequency and phenotype of peripheral B cell subsets seem unaffected, immune responses to T-cell-dependent and -independent antigens are substantially reduced. In vitro activation ofPrmt1 -deficient B cells with a variety of mitogens results in diminished proliferation, differentiation and survival, effects that are correlated with altered signal transduction from the B cell receptor. Thus PRMT1 activity in B cells is required for correct execution of multiple processes that in turn are necessary for humoral immunity. PRMT1 is an arginine methyltransferase involved in a variety of cell functions. Here the authors delete PRMT1 specifically in mature B cells to show the importance of arginine methylation for B cell proliferation, differentiation and survival, and thereby for humoral immunity.